Percepcija in razumevanje tolmačenja v slovenski znakovni jezik pri gluhih in naglušnih dijakih - Kulovec, Marjetka (Jezik in slovstvo, 2016)
The article describes a pilot study performed at the Institute for the Deaf and Hard of Hearing Ljubljana with the aim of investigating the level of understanding in a group of students who use sign language interpreting to follow classes. It also explores their preferences regarding interpreting style. The results are discouraging, given that students on average understand less than 50% of the content of classes, while it was not possible to clearly differentiate between interpreting styles within our experiment. The students' attitudes and preferences regarding sign language interpreting are also analysed. As the first research of its kind to be performed in Slovenia, the study addresses important issues regarding education of the deaf and hard of hearing population.
Keywords: Slovene; slovenščina; gluhi in naglušni dijaki; tolmačenje v slovenski znakovni jezik; razumevanje tolmačenja; tolmaški slog; stališča in preference